The possibility of developing intelligent logistics outsourcing in Slovenia - Bajec, Patricija (Transport, 2013)
Traditional outsourcing of logistics services has become an important tool for the Slovenian logistics and business market. It not only brings many benefits mainly in terms of cost reduction and focuses on core competencies, but also many shortcomings regarding business flexibility improvement and innovation development. As an increasingly competitive environment increases shipper's expectations, more innovative ways of outsourcing are needed, which would improve their flexibility and level of differentiation in order to capture greater market share. This indeed represents a departure from standard solutions and requires implementation of intelligent logistics solutions. Therefore, Slovenian logistics service providers face new challenges. The aim of this study is to examine the possibility of developing intelligent logistics outsourcing in Slovenia, and propose a method of planning and carrying out outsourcing, which will be advanced, and will bring benefits to both sides. For this reason, a general model of intelligent logistics outsourcing was developed based on a literature review of intelligent logistics outsourcing and a survey of the outsourcing market in Slovenia. According to our survey, Slovenian logistics providers are not mature enough for more intelligent means yet. Therefore, some suggestion that will significantly help and additionally motivate logistics service providers to use an intelligent logistics outsourcing model in order to offer more innovative solutions, as well as capture a greater market share were proposed. Using this model and these suggestions, it would be possible to create solutions in favour of intelligent outsourcing in Slovenia.First Published Online: 11 Oct 2013